2021
DOI: 10.1177/0263276420981614
|View full text |Cite
|
Sign up to set email alerts
|

Towards Neuroecosociality: Mental Health in Adversity

Abstract: Social theory has much to gain from taking up the challenges of conceptualizing ‘mental health’. Such an approach to the stunting of human mental life in conditions of adversity requires us to open up the black box of ‘environment’, and to develop a vitalist biosocial science, informed by and in conversation with the life sciences and the neurosciences. In this paper we draw on both classical and contemporary social theory to begin this task. We explore human inhabitation – how humans inhabit their ‘ecological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 103 publications
0
51
0
3
Order By: Relevance
“…As such, vulnerability may be seen as more than a "unhealthy state" of acquired susceptibility to risk and harm and heightened frailty; it also encompasses a sense of "genuine plasticity" and sensitivity (Taussig et al, 2013, p. s4) to one's inhabited environment, hence, a relational mode of being vulnerable to others. It is worth considering, therefore, (i) how the relational, social, and political ecologies of vulnerability play out in everyday life and (ii) whether the intertwining of the living and the milieu might be articulated not only in terms of its negative potential (i.e., risk, harm, exposure to stress) but also in terms of positive or transformative potentials, including processes of adaptation and socio-environmental affordances, as well as different forms of healing and repair (Kirmayer, 2019;Rose et al, 2021). We wonder, then, in what ways biosocial research and ecosocial theory might be bridged in a lively, processual perspective that "embraces a social production of disease perspective while aiming to bring in a comparably rich biological and ecological analysis, " as proposed by Nancy Krieger (2001, p. 672).…”
Section: Conclusion: From Biosocial Science To An Ecosocial Framing Of Vulnerability and The Living Milieumentioning
confidence: 99%
See 1 more Smart Citation
“…As such, vulnerability may be seen as more than a "unhealthy state" of acquired susceptibility to risk and harm and heightened frailty; it also encompasses a sense of "genuine plasticity" and sensitivity (Taussig et al, 2013, p. s4) to one's inhabited environment, hence, a relational mode of being vulnerable to others. It is worth considering, therefore, (i) how the relational, social, and political ecologies of vulnerability play out in everyday life and (ii) whether the intertwining of the living and the milieu might be articulated not only in terms of its negative potential (i.e., risk, harm, exposure to stress) but also in terms of positive or transformative potentials, including processes of adaptation and socio-environmental affordances, as well as different forms of healing and repair (Kirmayer, 2019;Rose et al, 2021). We wonder, then, in what ways biosocial research and ecosocial theory might be bridged in a lively, processual perspective that "embraces a social production of disease perspective while aiming to bring in a comparably rich biological and ecological analysis, " as proposed by Nancy Krieger (2001, p. 672).…”
Section: Conclusion: From Biosocial Science To An Ecosocial Framing Of Vulnerability and The Living Milieumentioning
confidence: 99%
“…Third, the living conditions of the "person-in-environment" seen as "embedded in an ecosocial crucible of interacting processes" (Filipe et al, 2020, p. 9) that warrant a combination of epigenetic, neurodevelopmental, longitudinal, socio-historical, and ethical empirical perspectives. Thus, alongside the philosophical unpacking of the vitality and normativity of human health and life as advanced by Georges Canguilhem, we have suggested that additional social scientific and empirical research attention should be paid to the people's everyday living conditions and to the social ecologies of adversity, precariousness, vulnerability, and marginalization (Han, 2018;Rose et al, 2021) as these affect people's health and their "life as such" (Fassin, 2009, p. 45;Filipe, 2014).…”
Section: Conclusion: From Biosocial Science To An Ecosocial Framing Of Vulnerability and The Living Milieumentioning
confidence: 99%
“…However, niches also represent possibilities for different activities, ways of life, and experiences. In this sense, Rose et al (2021) propose to expand this conception of niche, bringing it closer to the concept of Umwelt, inspired by the biologist Jakob von Uexküll (1982), reflecting the idea that different human beings inhabit different worlds of experience. Fuchs (2018) notes that many of the salient features of human Umwelten depend on culture, history, and political and economic context.…”
Section: /30mentioning
confidence: 99%
“…This example highlights the need to understand how niches interact with each other, opening up to specific types of psychological, emotional, and biological development (Fuchs, 2018;Rose et al, 2021). Those who experience psychic distress occupy niches, seeking to make a life for themselves, reconstructing and recreating their trajectories in a world rich in meanings, memories, and affections, and that offers certain ways of living and delimits others.…”
Section: /30mentioning
confidence: 99%
“…Although still in its infancy, neuroepigenetics is particularly salient as it arises at the crossroads of two trends that have attracted much attention over the last few decades: firstly, the biological embedding of social experience, meaning the process whereby life experiences produce “lasting changes in the function of a biological system with consequences for development, behavior, and health” ( Aristizabal et al, 2020 ). Secondly, what sociologist Nikolas Rose and colleagues have recently termed “neuroecosociality,” an integration of biological and social understandings that builds upon emerging findings from neuroscience to find mechanistic pathways that explain trajectories of well-being and disease ( Rose et al, 2021 ).…”
Section: Introduction: Biology Beyond the Genomementioning
confidence: 99%